An Algorithm for Summarizing Strategies Identification - Idris, N.; Mohd Sapiyan, B.; Abdullah, R. (2008)
Summarizing is a process of identifying important information from a text. Experts employ several important strategies to produce good summaries. Unfortunately, students do not acquire the summarization skills. Thus, this paper proposed an algorithm to identify the summarizing strategies employed by students using summary sentence decomposition. The strategies used by experts are identified and translated into a set of heuristic rules where the algorithm is developed based on the heuristic rules.